ANALISIS TINGKAT KESUKARAN, DAYA BEDA DAN EFEKTIVITAS PENGECOHpSOALpUJIAN AKHIRlSEMESTERlMATAlPELAJARAN EKONOMI SISWA SMA NEGERI 2 GUNUNG TALANG TAHUN AJARAN 2018/2019 - Eka sumanti; Dessi susanti (Jurnal Ecogen, 2019)
The purpose of this study, to analyze the level of difficulty, difference in power and distractors in economics questions odd semester XII IPA and Social Sciences in 2018/2019. From the analysis of the level of difficulty, it can be seen that out of the 10 items, there are 8 items analyzed which do not fulfill the good items. This is because according to Arikunto (2009: 207) a good question is a matter that has a moderate level of difficulty (not too easy and not too difficult). So that the above questions do not meet the good questions. it can be seen that there are problems related to the power of different questions, where from the results of the analysis that the problem cannot distinguish smart students from stupid students. Of the 10 questions above 1 question whose classification is good, then 9 questions have bad classifications that are not compatible with the theory. While according to Arikunto (2009: 211) defines different power about a process capable of problems that distinguish between smart students and students who are stupid. Of the 10 items analyzed, there are 4 items that are not effective in carrying out their functions as distractors, this is because according to Sudijono (2012: 410). Definition of the purpose of the installation of distractors so that students who take the test of learning outcomes are many who are interested in choosing the answer correctly. It is known that all of the above questions meet the low deception because of less than 5% of students choosing the function of the distractor effectivenessKeyword : level of difficulty, different power and distractors